(untitled) (Emancipação, 2018)
Resumo: O presente artigo busca discutir, brevemente, a concepção de currículo na perspectiva da educação emancipatória e refletir acerca do significado dessa concepção a partir das reflexões de Paulo Freire. A pesquisa desenvolvida no Mestrado em Educação da Universidade Federal de São Carlos deu origem a este artigo. No trabalho de pesquisa, foi desenvolvida a análise documental da Matriz Curricular da Rede Municipal de Ensino de Sorocaba (2012). Para buscar as respostas aos problemas de pesquisa, foi desenvolvida a análise do documento em estudo. Considerando as análises, foi possível apontar algumas questões relevantes relacionadas à presença de Freire no documento e, também, perceber contradições que expressam a apropriação ideológica do conceito de emancipação. Palavras Chave: Educação Emancipatória. Currículo. Freire. Abstract: The article seeks to discuss briefly the curriculum design from the perspective of emancipatory education and develops a reflection on the meaning of this concept from the contributions of Paulo Freire. The research developed in the Master of Education, Federal University of São Carlos gave rise to this article. In the research work has been developed to document analysis Curricular Matrix of Sorocaba’s Education Municipal System (2012). To search for answers to research problems has been developed to analyze the document under consideration. Considering the analyzes, it was possible to point out some important issuesregarding the presence of Freire in the document and also perceive contradictions that express ideological appropriation of the concept of emancipation. Keywords: Emancipation Education. Curriculum. Freire.